Sex differences in type I interferon production by plasmacytoid dendritic cells - Sampson, OL (2023)
The importance of immune sex differences is widely gaining recognition as critically important in determining differential outcome in health and disease between males and females. The female immune response is generally more pro-inflammatory and shows a greater TH2-skew than the male response which is generally more tolerant and TH1-skewed. Central to this difference the production of type I interferon (IFN-I) by the principal responsible cell type, plasmacytoid dendritic cells (pDCs), is greater in females as the upstream receptor, TLR7, is encoded by the X-chromosome and is biallelically expressed in ∼30% of female immune cells. However, study of pDCs is historically difficult as they constitute only 0.1-0.5% of peripheral blood mononuclear cells and their activity declines rapidly ex-vivo.